A method for the simulation and optimization of district heating systems with meshed networks. (1st January 2015) - Vesterlund, Mattias; Dahl, Jan
Highlights: Process integration is used to develop method for modeling district heating. A method to model complex district heating networks with loops is developed. The flow distribution in loops in complex district heating network can be analyzed. The influence from bottlenecks in complex district heating network can be analyzed. Optimal heat production for a multisource district heating network can obtained. Abstract: There are two main methods nowadays for modeling district heating systems, but a key disadvantage of both is that a real network containing loops cannot be described without artificial simplifications in order to eliminate those distinguishing features. However, loops are very common in mature networks that have developed a meshed structure, and make the distribution of mass and heat flows quite characteristic. For this reason, a new process integration method for modeling complex district heating systems containing loops is described in this paper. This method makes it possible to analyze how loops and bottlenecks affect the behavior of the network, as well as the distribution path of the thermal energy in it. The district heating system in the town of Kiruna (located in the north of Sweden) has a complex design with several loops and part of it is used in the paper as an example of application.